1977
DOI: 10.1136/bmj.1.6056.266
|View full text |Cite
|
Sign up to set email alerts
|

Fibreoptic endoscopic palliative intubation of inoperable oesophagogastric neoplasms.

Abstract: SummaryPalliative intubation for inoperable malignant strictures at the cardia was done on 16 occasions in 13 patients using fibreoptic endoscopy. Preliminary dilatation was performed, and the Celestin tube was mounted on an introducer and passed over a guide wire inserted with a fibreoptic endoscope. Only one death resulted from the procedure and all the 12 patients who left hospital were swallowing satisfactorily on discharge. The method provided a simple and relatively safe means of relieving dysphagia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 7 publications
1
27
0
1
Order By: Relevance
“…Management of these patients raises many problems. In the case of advanced oesophageal cancer, oesophageal dilatation and intubation of the malignant stricture is associated with a significant mortality and morbidity (Amman & Collis, 1970;Atkinson & Ferguson. 1977).…”
Section: Hwnan Studiesmentioning
confidence: 99%
“…Management of these patients raises many problems. In the case of advanced oesophageal cancer, oesophageal dilatation and intubation of the malignant stricture is associated with a significant mortality and morbidity (Amman & Collis, 1970;Atkinson & Ferguson. 1977).…”
Section: Hwnan Studiesmentioning
confidence: 99%
“…Dysphagia may be relieved by the insertion of a prosthetic tube through the neoplastic stricture, but the usual method of laparotomy and pull-through causes a high immediate mortality (Johnson et al 1976). In recent years methods of intubation utilizing fibreoptic endoscopy have been devised (Tytgat et al 1976, Atkinson & Ferguson 1977.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has clearly demonstrated that those who dilate severe strictures and place stents in a single session have unacceptably high perforation rates. 30 The technique for proper placement of any type of esophageal stent must include adequate pre-stent dilation. 3,29 The larger the diameter of dilation, the easier and safer stent placement will be.…”
Section: 2728mentioning
confidence: 99%
“…The unacceptable complication and mortality rates associated with plastic and silicone esophageal stents occurred after development of commercial insertion devices that were larger and more rigid than necessary. 30 The other major negative factor in plastic stent safety was the practice by some of rapid dilation of a malignant stricture at the same sitting the stent was placed. An apparatus that was too large and rigid, combined with overly vigorous dilation of malignant strictures, proved to be a dynamic duo with unfair mechanical advantage over a very diseased and weakened esophagus and patient.…”
Section: 2728mentioning
confidence: 99%